The Effect of Numbered Head Together Learning Model Assisted by Learner Worksheets on Mathematical Problem-solving Ability - Jefry Samuel; Tan Hian Nio; Kerdid Simbolon (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2025)
The purpose of this study is to determine whether there is a difference in problem-solving ability assisted by worksheets between students who apply the NHT and Expository learning models. To determine whether or not there is an increase in problem-solving skills assisted by worksheets between students who apply the NHT and expository learning models. This research involved VII-A and VII-B classes of SMP Negeri 50 Jakarta with Quasi Experimental Design. Data obtained from posttest scores, where the data is normal and homogeneous while the data from the gain is normal and inhomogeneous then using the Independent Sample T-Test test, the results: (1) There is no difference in the mathematical problem-solving ability of students with the treatment of NHT and expository learning models. The average posttest value of mathematical problem-solving ability that gets the NHT learning model treatment reaches 58.72 while with the expository learning model treatment reaches 49.57. (2) There is a difference in the improvement of mathematical problem-solving ability between students who apply the NHT and expository learning models. The average gain data value of the Experiment class reached 46.56 and n - gain reached 0.5660 while the Expository class data gain reached 31.58 and n - gain reached 0.4126.